Re-examining the effects of official development assistance on foreign direct investment applying the VAR model - Saori Ono; Takashi Sekiyama (Economies, 2022)
This study re-examined the effect of official development assistance (ODA) of five major donor countries (France, Germany, Japan, the United Kingdom, and the United States) on foreign direct investment (FDI) using panel data from 2003 to 2020. In addition to the system Generalized Method of Moments (GMM) with the gravity model, the Granger causality test and impulse response analysis with the panel VAR model was conducted. It was concluded that ODA did not necessarily have an effect on FDI since the 2000s. It is also suggested that the vanguard effect of Japanese ODA, as indicated by some previous studies, appeared mainly in the 1990s and may not be sustainable. The novelty of this study is to verify the effects of the ODA of major donors on FDI using new data from the 2000s onward, especially to reveal that the vanguard effect of Japanese ODA has not been observed since the 2000s. A limitation of this study is to determine only the presence or absence of a general trend at a statistically significant level. Therefore, further research on individual cases is expected to find how ODA has affected the investment decisions of individual companies.
Keywords: 330; foreign aid; foreign direct investment; Granger causality; gravity model; official development assistance; panel data; system GMM; VAR model